If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8.8x + 28.08 = -11.2x + 27 Reorder the terms: 28.08 + 8.8x = -11.2x + 27 Reorder the terms: 28.08 + 8.8x = 27 + -11.2x Solving 28.08 + 8.8x = 27 + -11.2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11.2x' to each side of the equation. 28.08 + 8.8x + 11.2x = 27 + -11.2x + 11.2x Combine like terms: 8.8x + 11.2x = 20x 28.08 + 20x = 27 + -11.2x + 11.2x Combine like terms: -11.2x + 11.2x = 0.0 28.08 + 20x = 27 + 0.0 28.08 + 20x = 27 Add '-28.08' to each side of the equation. 28.08 + -28.08 + 20x = 27 + -28.08 Combine like terms: 28.08 + -28.08 = 0.00 0.00 + 20x = 27 + -28.08 20x = 27 + -28.08 Combine like terms: 27 + -28.08 = -1.08 20x = -1.08 Divide each side by '20'. x = -0.054 Simplifying x = -0.054
| 2x+(x-30)+x=180 | | 5x^2+6y^2-10z^2+30=0 | | 72+3m+2(4-m)= | | 7.3x-2.8=19.1 | | 2=3(x-3)-(x-5) | | 2(6x-1)-5(x+6)=5(x+1) | | 7x+15-3x=12+(7*2+4*4)*2 | | 7+7(x-1)=4-4(x-5) | | 2(3-m)-3(4+m)= | | (x+3)*(3x-5)=10 | | 16y-3=31-y | | x^2+11=75 | | 7=5+u | | 7cosx+sinx=2 | | (5x-2)(x^2-7x+12)=0 | | 9(2n+2)=9(7n+6)+3 | | 6ln(2x+6)=26 | | 1+1=-2(7x-1) | | 15x^3-3x^2= | | 40y^2-217y-444=0 | | 4(2x+8)=-27+19 | | 7x+13=-5 | | 7x+15-5x=5x+11-5x | | 2(a+3)=6a+2 | | 1z+36=4z-4 | | X+2Y-Z=12 | | ln(3x-1)=ln(2-x)+1 | | 2x-(21-3)*3+5x=4x+3(2*4-3) | | 12(8c-1)-10=94c+12 | | 2(4v+1)-6= | | 8(x-8)=34-2x | | 0.34w=1.70 |